1989
DOI: 10.1086/269138
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interest and Public Opinion Toward Smoking Restrictions and Cigarette Taxes

Abstract: A burgeoning literature suggests that self-interest has little influence on policy preferences. In sharp contrast are the findings discussed in this paper: we show that self-interest plays a decisive role in shaping attitudes toward smoking restrictions and cigarette taxes. Data from two random samples of California adults collected by the Field Institute in April 1987 and February 1984 indicate that nonsmokers are far more enthusiastic about tightening smoking restrictions and increasing cigarette taxes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 24 publications
4
74
0
2
Order By: Relevance
“…While the symbolic and demand-oriented variables perhaps offer greater support, there is clear evidence that those working in the civil service and in public corporations have a strong preference for government delivery of services. Some past research, especially on racial policy (Sears et al 1980) stressed the importance of symbolic variables and the absence of a self-interest connection, but the present findings with regard to hospitals and public sector workers are in agreement with more recent work on issues such as gun control, smoking, and social security (Wolpert and Gimpel 1998;Campbell 2002;Green and Gerkin 1989) which point to the importance of self-interest variables.…”
Section: Discussionsupporting
confidence: 90%
“…While the symbolic and demand-oriented variables perhaps offer greater support, there is clear evidence that those working in the civil service and in public corporations have a strong preference for government delivery of services. Some past research, especially on racial policy (Sears et al 1980) stressed the importance of symbolic variables and the absence of a self-interest connection, but the present findings with regard to hospitals and public sector workers are in agreement with more recent work on issues such as gun control, smoking, and social security (Wolpert and Gimpel 1998;Campbell 2002;Green and Gerkin 1989) which point to the importance of self-interest variables.…”
Section: Discussionsupporting
confidence: 90%
“…If true, this would parallel the well-documented observation that self-interest drives citizens' policy preferences only when the personal costs and benefits of a policy are highlighted (Young et al 1991) or are especially clear (Chong, Citrin, and Conley 2001) or substantial (Green and Gerken 1989). Further research would be required to test these propositions about rational and psychological roots of trust.…”
Section: Methodological and Theoretical Implications: Integrating Socmentioning
confidence: 69%
“…local information, such as information about the local economy, and 2! mass media coverage of economic issues+ Citizens tend to process personallevel experiences and concerns in a fashion that compartmentalizes them from the political world+ 29 Collective-level information, on the other hand, is more easily linked to government policy+ An unemployed person is unlikely to blame the government for his or her personal situation, but people who are aware of rising joblessness in their country or community are likely to hold the government accountable for this development, regardless of their employment status+ In the case of trade preferences, if available information convinces a person that many in the United States are being adversely affected by free trade, even if he is not, it 25+ For a full review, see ibid+ 26+ Green and Gerken, for example, found that smoking-related policy preferences were significantly influenced by whether a person was a smoker+ The few exceptions are simple policies with straightforward effects on individuals, such as the effects of nonsmoking policies on smokers+ As complex, difficult to understand agreements, trade policies would not naturally fall into this category of policies in which one would expect self-interest to affect political preferences+ See Green andGerken 1989+ 27+ See Sears andFunk 1990;and Mutz 1992+ 28+ Kinder and Kiewiet 1981+ 29+ See, for example, Brody and Sniderman 1977and Mutz 1994+ will be the former, sociotropic perception that shapes his trade policy preferences rather than how trade has influenced his personal economic well-being+ To summarize, research on the role of economic well-being on political preferences would warn against the assumption of self-interest as the driving force behind attitudes toward trade+ Studies of mass opinion have repeatedly shown that individuals rarely form political preferences on the basis of economic self-interest+ Although early studies of U+S+ voting behavior attributed the surge enjoyed by incumbent parties in good economic times, and the anti-incumbent preferences in bad economic times, to so-called "pocketbook" voting, once these studies moved beyond aggregates to the individual level of analysis, it became clear that selfinterest was not the mechanism driving economic accountability+ The people helped or hurt by the economy were not those rewarding and punishing accordingly; instead, accountability rested on citizens' perceptions of how the nation as a whole was faring-perceptions that might or might not be accurate+…”
Section: The Origins Of Trade Preferencesmentioning
confidence: 99%